2021
DOI: 10.3389/fchem.2021.655983
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Semi-Continuous Extraction and In-Line Purification of High β-O-4 Butanosolv Lignin

Abstract: Innovative biomass fractionation is of major importance for economically competitive biorefineries. Lignin is currently severely underutilized due to the use of high severity fractionation methodologies that yield complex condensed lignin that limits high-value applicability. Mild lignin fractionation conditions can lead to lignin with a more regular C-O bonded structure that has increased potential for higher value applications. Nevertheless, such extraction methodologies typically suffer from inadequate lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 101 publications
2
23
0
Order By: Relevance
“…Analytical pyrolysis showed that when using the n-butanol/water solvent system, the obtained lignin-enriched fraction contains a significant (20.8 ± 0.4%) amount of carbohydrate admixtures, which are not detected using GC-FID alditol carbohydrate method of analysis. This can be explained by the formation of hydrolysis-stable n-butanol-carbohydrate ethers during the delignification process, as described in the literature [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical pyrolysis showed that when using the n-butanol/water solvent system, the obtained lignin-enriched fraction contains a significant (20.8 ± 0.4%) amount of carbohydrate admixtures, which are not detected using GC-FID alditol carbohydrate method of analysis. This can be explained by the formation of hydrolysis-stable n-butanol-carbohydrate ethers during the delignification process, as described in the literature [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent work at moderate temperatures (~100–150 °C) and using organic acids or low concentration of mineral acids allows us to obtain relatively low condensed lignin with a high amount of native β-O-4 bonds and good solubility in organic solvents [ 27 , 28 ]. Furthermore, extraction efficiency can be further enhanced using flow-through setups that lower the exposure time of released fragments to the reactive medium [ 29 , 30 ]. Use of organic solvents in separation allows us to increase the efficiency of the process when compared to dilute acid hydrolysis methods due to the increase of lignin solubility in the used process medium.…”
Section: Introductionmentioning
confidence: 99%
“…Another positive effect of this type of irradiation is that it has led to a higher selectivity of the reaction and less unwanted side reactions and bye-products, such as condensation and degradation reactions [ 11 ]. The lower residence time of the lignin in the acidic reaction media at high temperatures during microwave extraction reduces these risks and leads to higher-quality lignin [ 36 ]. Considering all these advantages, it comes as no surprise that microwave irradiation has also been explored in applications for lignocellulosic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is about lignin's variability in nature that is quite heterogeneous (as already mentioned in this chapter); therefore, its isolation will produce a mixture of products, apart from being a challenging task and less economically feasible to purify all the different compounds for further applications [45,71]. The second point is related to the lignin fractionation methodologies that yield complex condensed lignin, which limits its high-value applicability [71,94], difficulties in attaining lignin in high yield and with good chemical and physical properties (e.g., molecular weight distribution, solubility, reactivity and number of functional groups), and with quality (in relation to the inter-units linkages, condensed lignin is not attractive) [43,95]. The third point is associated with LNP production and their adequate stabilization for different applications [96].…”
mentioning
confidence: 99%